A hydrophobic photouncaging reaction to profile the lipid droplet interactome in tissues - Di Shen; Qun Zhao; Huaiyue Zhang; Ci Wu; Hao Jin; Kun Guo; Rui Sun; Hengke Guo; Qi Zhao; Huan Feng; Xuepeng Dong; Zhenming Gao; et al. (Proceedings of the National Academy of Sciences, 2025)
Most bioorthogonal photouncaging reactions preferentially occur in polar environments to accommodate biological applications in the aqueous cellular milieu. However, they are not precisely designed to chemically adapt to the diverse microenvironments of the cell. Herein, we report a hydrophobic photouncaging reaction with tailored photolytic kinetics toward solvent polarity. Structural modulations of the aminobenzoquinone-based photocage reveal the impact of cyclic ring size, steric substituent, and electronic substituent on the individual uncaging kinetics ( k H2O and k dioxane ) and polarity preference ( k dioxane / k H2O ). Rational incorporation of optimized moieties leads to up to 20.2-fold nonpolar kinetic selectivity ( k dioxane / k H2O ). Further photochemical spectroscopic characterizations and theoretical calculations together uncover the mechanism underlying the polarity-dependent uncaging kinetics. The uncaged ortho-quinone methide product bears covalent reactivity toward diverse nucleophiles of a protein revealed by tandem mass spectrometry. Finally, we demonstrate the application of such lipophilic photouncaging chemistry toward selective labeling and profiling of proteins in proximity to lipid droplets inside human fatty liver tissues. Together, this work studies the solvent polarity effects of a photouncaging reaction and chemically adapts it toward suborganelle-targeted protein proximity labeling and profiling.